基于ANSYS的平面凸轮有限元模态分析 - 李瑞虎; 王凯; 谢国灿 (Jixie chuandong)
The theory of modal analysis is introduced. Through modal analysis of the plate cam, the inherent frequencies, mode shapes, relative displacement and relative stress distribution map of the first 10 modes are obtained respectively by ANSYS software. The results of the relative distribution of the vibration magnitude in the cam are given, which provide necessary guides for the dynamic optimal design of the plate cam.